(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2017)
The article proposes to analyze the criticisms made by Luigi Pirandello (On Humor, 1908) and Carlo Michelstaedter (Persuasion and Rhetoric, 1909-1910) in regard to the classical idea of Rhetoric. It also proposes to show how the two different approaches derive from differing interpretations of the new modernist themes. For Pirandello, referring to the principles of imitation of the rules of rhetoric means to repropose, in works of art, universally accepted truths, suppressing in them the new modernist awareness that has upset the previous direct link between life and representation; Michelstaedter, instead, believes that the rejection of the old Rhetoric does not erase the imitative relation, because with the loss of the timeless referent of the metaphysical idea of Truth, the «mimetic regime» is simply shifted onto the historical referent of social consent. Pirandello’s analysis, based on the contrast between Life and Truth, becomes – in Italy – the perfect mirror of the new modernist themes regarding the inability of assuming Reality in the symbolisms of the I. Michelstaedter’s analysis of the same issues is meticulous but also critical, and he concludes that the crisis of the concept of Truth does not lead to the liberation of the Subject from the confines of metaphysical thought but forces it into the mimetic regime of a Truth that is, from time to time, the dominant ideology of a particular moment in history.